Digitalization in Urban Water Governance: Case Study of Bengaluru and Singapore - Banerjee, Chandan; Bhaduri, Anik; Saraswat, Chitresh (Frontiers in Environmental Science, 2022)
Urban water governance aims to ensure equitable access to adequate quality water and related services to rapidly growing urban population while protecting the environment. Rapid urbanization and changing climate are posing challenges to the formal and informal institutions responsible for governing and managing water resources. Complexities existing due to the interaction between societal and environmental subsystems of urban water cycle adds pressure on institutional capabilities to cope up with various uncertainties. Emergence of digital technologies has provided the necessary tools in urban water governance to strengthen capabilities through effective monitoring, decision making, and forecasting. The paper examines the claim that employing digital technology can help mitigate various problems and challenges faced in urban water governance. The paper analyses three digital technologies using the case studies of Bengaluru and Singapore to understand the transformation pathways in urban water governance. The paper indicates that to unlock the full potential and derive best returns of investment, digitalization needs to have broader objectives. Multi-purpose use of digital tools can contribute effectively to the implementation of Integrated Urban Water Management (IUWM). The results highlighted that societal acceptability of digitalization depends majorly on the mode of implementation and not so much on the technology.